2007
DOI: 10.1029/2007gl029733
|View full text |Cite
|
Sign up to set email alerts
|

Arctic and Antarctic polar winter NOx and energetic particle precipitation in 2002–2006

Abstract: [1] We report GOMOS nighttime observations of middle atmosphere NO 2 and O 3 profiles during eight recent polar winters in the Arctic and Antarctic. The NO 2 measurements are used to study the effects of energetic particle precipitation and further downward transport of polar NO x . During seven of the eight observed winters NO x enhancements occur in good correlation with levels of enhanced high-energy particle precipitation and/or geomagnetic activity as indicated by the A p index. We find a nearly linear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
117
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(122 citation statements)
references
References 14 publications
5
117
0
Order By: Relevance
“…They then used a chemistry general circulation model to simulate surface temperature response to geomagnetic activity variations by realistically varying the A p index to further explore the mechanisms leading to the temperature responses reported earlier by Rozanov et al [2005]. The A p -driven NO x parameterization that they used in their model had previously proved to be realistic and in a good agreement with observations [Baumgaertner et al, 2009], concurring well with earlier observations of the relationship between polar middle atmosphere NO x concentrations and the variation in geomagnetic activity and particle precipitation [Siskind et al, 2000;Randall et al, 2007;Seppälä et al, 2007;Sinnhuber et al, 2011]. Baumgaertner et al [2011] showed the temperature response from 0.01 hPa to 1000 hPa (mesopause to surface) when the model was forced with the A p -controlled EPP-NO x (their Figure 9).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…They then used a chemistry general circulation model to simulate surface temperature response to geomagnetic activity variations by realistically varying the A p index to further explore the mechanisms leading to the temperature responses reported earlier by Rozanov et al [2005]. The A p -driven NO x parameterization that they used in their model had previously proved to be realistic and in a good agreement with observations [Baumgaertner et al, 2009], concurring well with earlier observations of the relationship between polar middle atmosphere NO x concentrations and the variation in geomagnetic activity and particle precipitation [Siskind et al, 2000;Randall et al, 2007;Seppälä et al, 2007;Sinnhuber et al, 2011]. Baumgaertner et al [2011] showed the temperature response from 0.01 hPa to 1000 hPa (mesopause to surface) when the model was forced with the A p -controlled EPP-NO x (their Figure 9).…”
Section: Introductionsupporting
confidence: 79%
“…It is now well known that ionization from particle precipitation during geomagnetic activity provides a direct chemical coupling mechanism from the Sun to the atmosphere via the production of NO x and HO x , constituents which are important to middle atmosphere ozone balance [e.g., Randall et al, 2005;Seppälä et al, 2007;Verronen et al, 2011;Andersson et al, 2012]. Geomagnetic activity driven signatures have been found in various meteorological and climate records [e.g., Lu et al, 2008a;Seppälä et al, 2009;Lockwood et al, 2010], but it has remained unclear which mechanism or mechanisms would be responsible for communicating geomagnetic activity variations to climate variables such as stratospheric and tropospheric temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…This depletes the radiation belts and has potentially important consequences for the atmosphere and climate change (e.g. Seppälä et al, 2007).…”
Section: Introduction and Applicationmentioning
confidence: 99%
“…In the recent years, observations have shown that during winter times NO x can be effectively transported downwards inside the polar vortex (Funke et al, 2005(Funke et al, , 2007Hauchecorne et al, 2007;Seppälä et al, 2007;, after NO x is produced by particle precipitation in the mesosphere-lower thermosphere (MLT). Although the satellite observations of NO x often cover altitudes up to middle mesosphere only, the connection to lower thermospheric NO x production has been established using VLF (Very Low-Frequency) radio propagation data in the case of the 2004 descent event (Clilverd et al, 2006).…”
Section: Introductionmentioning
confidence: 99%